The Influence of Acceptance and Commitment Therapy (Act) anxiety disorders in Patients at Limboto Health Center - Nanda Nurhalizah; Sabirin B. Syukur; Nur Uyuun I. Biahimo; Andi Safutra Suraya (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Anxiety disorders not only impact an individual's psychological state, but also affect social functioning, productivity, and quality of life. One of the psychotherapy approaches that is developing to overcome anxiety is Acceptance and Commitment Therapy (ACT). This study aims to determine the effect of Acceptance and Commitment Therapy (ACT) on the level of anxiety of patients at Limboto Health Center. This study uses a quasi-experimental method with a one group pre-test and post-test design approach. The population in this study is all adult patients who experience anxiety at the Limboto Health Center, with a sampling technique using purposive sampling, so that a sample of 18 respondents was obtained. Data analysis was carried out using the Wilcoxon test because the data was abnormally distributed. The results showed that before the intervention, there were 6 respondents with mild anxiety and 12 respondents with moderate anxiety. After being given ACT therapy, the number of respondents with mild anxiety increased to 17 people, while moderate anxiety decreased to 1 person. The Wilcoxon test showed a significance value of p = 0.000 (p < 0.05), which indicates a significant effect of ACT therapy on reducing anxiety levels. This study concluded that Acceptance and Commitment Therapy (ACT) was effective in lowering anxiety levels.